Inflammatory effects of high and moderate intensity exercise - Cerqueira, Érica Orlando Bompastor (2019)
Background: Exercise leads to a robust inflammatory response mainly characterized by the mobilization of leukocytes and an increase in circulating inflammatory mediators produced by immune cells and directly from the active muscle tissue. Both positive and negative effects on immune function and susceptibility to minor illnesses were observed. While engaging in moderate activity may enhance immune function above sedentary levels, excessive amounts of prolonged, high-intensity exercise may impair immune function. The goal of this systematic review was to clarify the inflammatory effects in response to different exercise intensities. Methods: A systemic search examining exercise and inflammation was performed on PubMed and completed on July 31st, 2017. Eighteen articles were included, and their quality was assessed. The specific components that were examined included circulating blood levels of cytokines, leukocytes, creatine kinase (CK) and C-reactive protein (CRP). Results: Most of the intervention studies showed changes in the assessed biomarkers, although these changes were not always consistent. White blood cells (WBC) had an increase immediately after intensive exercise (> 64 % VO2max), without alteration after moderate exercise (46 - 64% VO2max). The results suggested an elevation of the pro-inflammatory cytokines, namely IL-6, followed by an elevation of IL-10 that were more evident after intensive exercise bouts. CRP increased both after intense and moderate exercise, with peak increases up to 28h. CK increased only after intensive and long exercitation. Conclusion: It is suggested a particularly caution due to increased susceptibility to illness when higher exercise intensities are used.